Policy Research on African Agriculture: Trends, Gaps, and Challenges - Omamo, Steven Were (International Service for National Agricultural Research, 2003)
The central argument in this report is that most policy research on African agriculture is irrelevant to agricultural and overall economic policy in Africa, and that the policy research community-and the agricultural economics profession in particular-must shoulder a significant part of the blame for this state of affairs. A wide-ranging review of recent research reveals that agricultural economists have failed to put Africa's agricultural problems on the policy agenda in more than abstract fashions. We have failed to come to grips adequately with the real problems facing agricultural policymakers, namely, how to assess the operational feasibility of alternative policy options, and how to promote the feasibility of the most highly valued alternatives. A different approach to agricultural policy research is therefore suggested, built more on 'how' questions and less on 'what' questions and 'why' questions. Implications of such an approach for research design and conduct are drawn. Piloting action research in case studies of initiatives involving promising institutional innovations offers scope for identifying convincing 'how' answers. To implement such approaches, agricultural economists and other policy researchers require new skills and partnerships